Superparamagnetic Micelles for the Magnetic Hyperthermia Against Glioblastoma: A Multiphysics Approach for Personalized Treatment Planning - Matteo Bruno Lodi; Eleonora Matilde Angela Corda; Wirat Assawapanumat; Gian Luca Chabert; Francesco Desogus; Luca Saba; Andrea Perra; Norased Nasongkla; Alessandro Fanti; Giuseppe Mazzarella (IEEE Open Journal of Nanotechnology)
The treatment of diffuse, high-grade gliomas, the most aggressive form of primary brain tumors, poses significant therapeutic challenges. Recurrent high-grade gliomas are associated with a median overall survival of less than one year; therefore, new therapeutic strategies must be sought. In this work we propose the synthesis of novel superparamagnetic iron oxide (SPIO), following thermal decomposition in hexadecanediol, oleic acid and oleylamine, then assembled in micelles for brain tumor treatment. The resulting SPIO-micelles are preliminary characterized by an average diameter of 26 nm and a saturation magnetization of 56 emu/g, thus holding great potential for magnetic hyperthermia treatment (MHT). In this work a multiphysics nonlinear model for ad-hoc MHT planning based on patient-specific geometries has been developed. The model accounts for the convection-enhanced delivery (CED) computing the SPIO-micelles concentration patterns, coupling the mass transport to the RF problem, assuming a frequency- and spatial-dependent magnetic susceptibility. Given that the RF field is produced by a pair of Helmholtz coils, while considering the temperature-dependent variation of electromagnetic and thermal properties of normal and neoplastic brain tissue, the efficiency of the MHT was evaluated for different tumor geometries. The findings highlight that using realistic tumor geometries strongly affect treatment parameters (e.g., ∼32% and 1.2°C differences in the magnetic field and in the max. average tumor temperature). The radio-sensitization and equivalent dose distribution are studied, stressing the adjuvant potential of the novel SPIO-micelles formulation. The results also highlight that the proposed model could ensure precise hyperthermia treatment using RF MHT, confirming its potential for personalized cancer therapy. This research provides an important foundation for exploring the therapeutic possibilities of this novel approach, facilitating the development of tailored treatments for patients.